Long-term outcome over a decade after first rib resection for neurogenic thoracic outlet syndrome. (20th June 2021) - Nuutinen, Henrik; Kärkkäinen, Jussi M; Mäkinen, Kimmo; Aittola, Voitto; Saari, Petri; Pesonen, Janne
Abstract: : OBJECTIVES: The aim was to determine long-term outcomes over a decade after first rib resection (FRR) in patients with neurogenic thoracic outlet syndrome (NTOS). A secondary aim was to investigate correlation of residual rib stump with long-term symptoms. METHODS: This ambispective cohort included patients who underwent transaxillary FRRs for NTOS between 1998 and 2007. Short-term outcomes at 3-month clinical follow-up were retrospectively collected from medical records. Patients who agreed to participate in the study were invited to a long-term clinical follow-up in 2019. Disabilities of Arm, Shoulder, and Hand Score and Cervical Brachial Symptom Questionnaire were used. A chest X-ray limited to a clavicular projection was taken, and the length of the residual first rib was measured. RESULTS: Twenty patients mean age 41.8 [standard deviation (SD): 10.3 years] who underwent 27 FRRs participated in the study. The mean follow-up time was 14.9 (SD: 3.6) years. Excellent or good recovery was noted after 16 (59.3% of operated arms) operations in the short-term follow-up and 22 (81.5%) operations in the long-term follow-up. No reoperations were necessary for residual symptoms. The mean Cervical Brachial Symptom Questionnaire score was 26.7 (SD: 28.2) (maximum 120), and the Disabilities of Arm, Shoulder, and Hand Score was 21.1 (SD: 18.4) (maximum 100) points. Twenty-six patients (96.3%) had a noticeable residual first rib stump. The mean length of the residual first rib was 28.9 (SD: 9.5) mm. More than 30-mm rib stump did not indicate a worse long-term outcome. CONCLUSIONS: This study showed good long-term outcome without symptom recurrence after FRR for NTOS. In most patients, after surgery, quality of life and ability to work improved. Residual rib stump length was not associated with the treatment outcome. Abstract : The most common type of thoracic outlet syndrome (TOS) is neurogenic (NTOS) [1].